“I was… Until… Since then…”: Exploring the Mechanisms of Selection in a Tragic Narrative - Spector-Mersel, Gabriela (Narrative Works)

(untitled) (The University of New Brunswick, 2014)
This paper presents a reading of Amos’s life story that follows an interpretive model based on mechanisms of narrative selection (Spector-Mersel, 2011). Drawing on the notion of the narrative paradigm, this model is derived from narrative epistemology, and specifically from a conceptualization of how identities are claimed through stories. The narrative production is conceived of as consisting of six mechanisms of selection, through which biographical facts are sorted, with the purpose of confirming an end point. Accordingly, the analysis seeks to identify the expressions of these mechanisms in the story, as a means to recognize the identity being claimed. The examination of the mechanisms of selection displayed in both the content and the form of Amos’s story reveals a split end point, which divides Amos’s life into “before” and “after” the stroke. The “I was” part strictly corresponds with the cultural ideal of a Sabra-Kibbutz member, depicting Amos’s prior self as a “culturally appropriate” and highly significant figure in his collective. In contrast, the “since then” part, which portrays the past 15 years since the stroke as an extended present, conveys his being “outside” of both the culture and the collective. Considering Amos’s story a clear instance of a tragic narrative, some insights are offered that can shed light on possible manifestations of this story genre.